Preprocedural platelet transfusion for patients with thrombocytopenia undergoing interventional radiology procedures is not associated with reduced bleeding complications. Issue 4 (28th January 2017) - Warner, Matthew A.; Woodrum, David; Hanson, Andrew; Schroeder, Darrell R.; Wilson, Gregory; Kor, Daryl J.
Abstract : BACKGROUND: Platelet (PLT) transfusion before interventional radiology procedures is commonly performed in patients with thrombocytopenia. However, it is unclear if PLT transfusion is associated with reduced bleeding complications. STUDY DESIGN AND METHODS: This is a retrospective cohort study of adults undergoing interventional radiology procedures between January 1, 2009, and December 31, 2013. Baseline characteristics, coagulation variables, transfusion requirements, and procedural details were evaluated. Propensity‐matched analyses were used to assess relationships between PLT transfusions and the outcomes of interest, including a primary outcome of periprocedural red blood cell (RBC) transfusion during the procedure or within the first 24 hours after procedure. RESULTS: A total of 18, 204 participants met inclusion criteria, and 2060 (11.3%) had a PLT count of not more than 100 × 10 9 /L before their procedure. Of these, 203 patients (9.9) received preprocedural PLTs. There was no significant difference in RBC requirements between those receiving or not receiving preprocedural PLTs in propensity‐matched analysis (odds ratio [OR],  1.45; 95% confidence interval [CI], 0.95‐2.21; p = 0.085). PLT transfusion was associated with increased rates of intensive care unit admission (OR [95% CI],  1.57 [1.07‐2.32]; p = 0.022). CONCLUSION: In patients with thrombocytopenia undergoing interventional radiology procedures, preprocedural PLT transfusion was not associated with reduced periprocedural RBC requirements. These findings suggest that prophylactic PLT transfusions are not warranted in nonbleeding patients with preprocedural PLT counts exceeding 50 × 10 9 /L. Future clinical trials are needed to further define relationships between prophylactic PLT administration and bleeding complications, especially at more severe levels of thrombocytopenia or in the presence of PLT dysfunction.